دراسة تأثير بعض عمليات الخدمة الزراعية في ظاهرة المعاومة عند صنف الحمضيات اليوسفي "الكليمانتين" - دواي فيصل; مخول جرجس; دنورة إياد (Latakia University Journal -Biological Sciences Series, 2019)
شملت الدراسة تأثير كل من معاملات ( التقليم، تحليق الأغصان، السماد الورقي المتوازن، الرش بحمض الجبرلين) في ظاهرة المعاومة عند صنف الحمضيات اليوسفي الكليمانتين (Citrus reticulate var Clementin , Blanco ) من خلال التأثير في الإنتاج السنوي للأشجار وما يرافق ذلك من تغيرات في بعض الصفات الفيزيائية والكيميائية للثمار وذلك خلال موسمي (2008 – 2007). وقد بينت الدراسة بأن أفضل المعاملات من حيث الإنتاج هي معاملة التقليم تلتها معاملة التسميد الورقي المتوازن. وبالنسبة لمعاملتي تحليق الأغصان والرش بحمض الجبرلين في فترة الإزهار فقد أدتا إلى تغيير كمية الإنتاج بالاتجاه المطلوب و لكن ليس بالدرجة الكافية لتحقيق الإنتاج المتوازن. أما عن تأثير الرش بحمض الجبرلين في فترة تمايز البراعم فقد زاد الإنتاج في سنة الحمل الغزير. مما سبق يتبن بأن أفضل المعاملات هي معاملة التقليم من حيث الإنتاج المتوازن للموسمين مع تحقيق مواصفات نوعية جيدة للثمار تليها معاملة التسميد الورقي المتوازن. This study involved the effect of the following treatments (pruning, girdling branches, stable leaf fertilizer, and spraying with gibberellins acid) in alternate phenomenon of Clementine mandarin cultivar (Citrus reticulate var. Clementine, Blanco) through the effect on the annual production of trees, and associated changes in some physical and chemical characteristics of fruits during 2007-2008 growing seasons. This study showed that the best treatment for production was pruning followed by leaf stable fertilizer treatment. Ringing branches and spraying with gibberellins acid at the flowering stage led to insufficient changes in production quantity and not for a suitable degree to establish the stable production; but spraying with gibberellins acid during distinguishing buds has increased yield production. It could be summarized that the pruning treatment is the best for a balanced production for two seasons and for the achievement of good quality characteristics, followed by the stable leaf fertilizer treatment